2010
DOI: 10.1111/j.1528-1167.2009.02491.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired maturation of cortical GABAA receptor expression in pediatric epilepsy

Abstract: SUMMARY Purpose Expression of the protein subunits that make up the GABAA receptor pentamer is known to change during postnatal brain development in animal models. In the present study, analysis of cortical GABAA subunit expression was performed in control human tissue obtained from infancy through adolescence, and was compared to that from similarly aged children with intractable focal epilepsy. Methods Twenty frozen pediatric control and 25 epileptic neocortical specimens were collected. The membrane frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 46 publications
1
40
1
Order By: Relevance
“…(Sowell et al, 2003). In addition to synaptic density, age-dependent neurochemical processes are also known to change with development and maturation (Jansen et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Sowell et al, 2003). In addition to synaptic density, age-dependent neurochemical processes are also known to change with development and maturation (Jansen et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…However, both the subunit composition neuronal GABA a receptors and functional role changes during prenatal and postnatal development in humans (Andersen et al, 2002; Brooks-Kayal and Pritchett 1993; Kanaumi, et al, 2006; Reichelt et al, 1991). Due to elevated intracellular Cl- concentrations in immature neurons, GABA signaling in neonatal brain acts as an excitatory neurotransmitter – which switches to an inhibitory neurotransmitter after about the first 2 years of life (Jansen et al, 2010). In addition, GABA a receptor α1 and γ 2 subunit expression are known to increase over the first 5–6 years of life before reaching a plateau, whereas α4 subunit expression decreases during this same time period (Jansen, et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other details regarding these antibodies are provided in Supplemental Table 1. Frozen cortical tissue specimens (100–200 mg) were processed to isolate the membrane fraction and subjected to Western blot analysis as detailed in [14]. Infrared fluorescence was used for signal detection and quantitation (Odyssey Infrared Imaging System, LI-COR Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that neonatal seizures that arise by 24 h after HI are associated with similar alterations to GABAAR subunit changes that have previously been observed following SE and in chronic epilepsy (Lauren et al 2005, Wasterlain et al 2009, Jansen et al 2010. In HI-Sz animals we observed a significant reduction of GABAAR α3…”
Section: Discussionsupporting
confidence: 79%